ANALISIS TINGKAT KESEHATAN BANK PADA PT. BANK NEGARA INDONESIA (PERSERO), TBK DENGAN MENGGUNAKAN METODE RGEC - Cicilia Erly Istia (Jurnal Ilmiah Ekonomi Bisnis, 2020)
This study aims to analyze the health level of PT. Bank Negara Indonesia (Persero), Tbk for the period of 2016 - 2019 using the RGEC (Risk Profile, Good Corporate Governance, Earnings, and Capital) methods. This type of research is descriptive with a quantitative approach. Assessment results show that: (1) the level of bank health in terms of the risk profile aspects of 2016 to 2019 are in the good category (2) the level of bank health in terms of Good Corporate Governance in 2016 - 2019 are at a healthy composite value (3) health level banks in terms of Earnings in 2016 to 2019 both categories with the efforts of the bank to increase income (4) the soundness of the bank in terms of Capital in 2016 - 2019 classified as healthy (5) assessment of the soundness of the bank is still in the good category and the bank continue to improve performance to face the risks faced in the future.